Buscando significações na aprendizagem de inglês no ensino médio: uma experiência de fomento de autonomia - NATIVIDADE, Elda Carla Barata (Universidade Federal do Pará, 2011)
It presents the results of a research in the field of Language Teaching and Learning which aimed at developing students autonomy regarding their appropriation of English as a foreign language in a country school. The study was developed as an imposing need to make English learning meaningful and motivating to students in this school. Motivation was seen as an important element in the construction of this knowledge. The study relied on previous research by Brown e Jacob (apud WILLIAN et al, 2004) e Harmer (2001), and on motivation; and Holec (apud PAIVA, 2005), Dickinson (1994), Little (1991), Benson (2001), and Paiva (2007) on autonomy in foreign languages learning. Methodological guidelines were borrowed from Hadley (2004) and Viana (2007) and especially on how to conduct data collection, organization, and analysis in an action - research format. This study was conducted by he teacher-researcher, based on data collected by the author in her High School freshman class with twenty eight students enrolled in the evening class of a public school in São Francisco do Pará. The data analysis proved that a meaningful learning must have students‟ daily life as a starting point to any activity. It also proved that situations which demand students using the language in real contexts makes learning more meaningful to them at the same time that it fosters autonomy. The activity conducted for this study, called Posters‟ show, aimed at developing quality behavior in students towards learning because, taking autonomy as a background, students‟ daily life, their life experiences, and their responsibility towards the learning situation are far more important elements to experience than mastering grammar rules or even covering the complete content of each academic year. Results showed that positive outcomes because a change occurred in students perceptions on learning, evidencing that it is possible to enhance autonomous attitudes when proper guidance is given to students.